What can proximate determinants of fertility tells us about the fertility transition of Pakistan? - Jamal Abdul Nasir; Andrew Hinde; Sabu Padmadas (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
Lanka, Bangladesh are started about the same time as that in Pakistan and there has been a considerable reduction in fertility in these countries. During the past five decades Pakistan experienced a slow pace change in fertility-total fertility rate has declined from eight children per woman in the early 1960s to only four by the end of 2000s. Pakistani fertility particularly at regional levels received less attention in previous research. This paper attempts to explore the role of main proximate determinants of fertility proposed by Bongaarts to analyse the fertility transition in Pakistan since 1990s. Using the crosssectional data from the 1990, 2006 and 2012 Pakistan Demographic and Health Survey, and 2000-01 Pakistan Reproductive Health and Family Planning Survey, the classical Bongaarts model is applied here and the analysis is extended to analyse the regional variation. The results indicate that timing of marriage and contraceptive use are crucial determinants associated with fertility reduction in Pakistan. By following the Bongaarts criteria of fertility transition, it can be concluded that Pakistan has entered in the early third phase of fertility transition. Specifically urban areas of Pakistan, two provinces Punjab and Baluchistan are ahead in fertility transition compared to other regions. The results of the analysis highlight various areas for program intervention and policy development in Pakistan.
Keywords: 330; Bongaarts model; family planning; Pakistan